1973
DOI: 10.1037/h0035007
|View full text |Cite
|
Sign up to set email alerts
|

Lateral inhibition and cognitive masking: A neuropsychological theory of attention.

Abstract: A neuropsychological theory of attention is described in which the encoding of one stimulus interferes with the encoding of other stimuli. This interference effect is termed cognitive masking and is attributed to recurrent lateral inhibition between neurons in association cortex. Evidence is reviewed which indicates that there is a facilitation of cortical recurrent inhibition during arousal, and it is suggested that cognitive masking is related to the level of arousal. A mathematical model is presented which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
1
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 56 publications
3
92
1
1
Order By: Relevance
“…In real biological systems, however, excitation or activation by itself is insufficient, and almost always requires to be balanced by inhibition. This too is also common in many artificial networks of cognition, particularly in the cases of perception and selective attention (Walley and Weiden, 1973;McClelland and Rummelheart, 1981). This balancing act, so to speak, is often modeled after a physiological process that is expressed at the cellular level of local neural circuits, known as recurrent inhibition.…”
Section: Neural Circuit Model Of Schizophreniamentioning
confidence: 99%
“…In real biological systems, however, excitation or activation by itself is insufficient, and almost always requires to be balanced by inhibition. This too is also common in many artificial networks of cognition, particularly in the cases of perception and selective attention (Walley and Weiden, 1973;McClelland and Rummelheart, 1981). This balancing act, so to speak, is often modeled after a physiological process that is expressed at the cellular level of local neural circuits, known as recurrent inhibition.…”
Section: Neural Circuit Model Of Schizophreniamentioning
confidence: 99%
“…A third way of handling both facilitation and inhibition from semantically related primes is to assume that there are both excitatory and inhibitory connections between related nodes in the memory network (see Martindale, 1981, andWalley &Weiden, 1973). According to this view, inhibitory priming effects are similar to lateral inhibition effects that occur in the visual sensory system (e .g., Ratliff, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Selective attention refers to the capacity to process target stimuli and ignore other, irrelevant and potentially interfering stimuli. Numerous experimental data in the literature suggest that the neurophysiological basis of selective attention could lie in the inhibition of neural responses to the irrelevant aspects of the stimulation (Walley and Weiden, 1973;Desimone and Duncan, 1995;Clark, 1996). It has been shown that the unitary responses of neurons in the visual cortex to unattended stimuli were dramatically reduced (Moran and Desimone, 1985).…”
Section: Introductionmentioning
confidence: 99%